THE EFFECTIVENESS OF SOLVENT PROPORTIONS ON ANTIOXIDANT PROPERTIES OF WANGON (Olax psittacorum (Wild.) Vahl.) LEAVES - Harjanti, Reslely; Aisiyah, Siti; Nopiyanti, Vivin (SEKOLAH TINGGI ILMU FARMASI YAYASAN PHARMASI SEMARANG, 2018)
The aim of this research was to find out the proportion of food grade and effective ethanol solvent to extract antioxidant phytoconstituents in wangon leaves. This study used 50%, 70% and 96% ethanol solvent. Wangon leaves were extracted with soxhlet method to produce the corresponding extract. Then the extract was tested for its antioxidant activity and the levels of the compound suspected to be active as an antioxidant compound including flavonoids and phenolic total were determined. The results showed that the best solvent proportion for extracting wangon leaves to have the greatest antioxidant activity was 96% ethanol. It was proved that 96% ethanol extract has potency as antioxidant with IC50 value equal to 71,27 ppm better than 50% and 70% ethanol extract. The 96% ethanol extract also had the greatest flavonoid and phenolic content of 99.44 ± 1.27mg Quercelia equivalent (QE)/g samples and 121.66 ± 1.39 mg Gallic acid equivalent (GAE)/g samples. The content of flavonoid and phenolic phytoconstituents in the extract has a linear correlation and was strongly associated with its antioxidant activity.